Solve for x.
13(x - 3) = 39
x = 1
x = 4
x = 6
x = 10

Question

Asked 11/6/2013 8:17:04 AM

Updated 5/24/2014 9:59:05 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [5/24/2014 9:59:03 AM]

Rating

3

13(x - 3) = 39

13x - 39 = 39

13x = 39 + 39

13x = 78

x = 78/13

x = 6

13x - 39 = 39

13x = 39 + 39

13x = 78

x = 78/13

x = 6

Added 5/24/2014 9:59:05 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/24/2014 10:53:51 AM]

Solve for x.
7(x - 3) + 3(4 - x) = -8
x = 1/4
x = 25/10
x = -16/19
x = -41/10

Question

Not Answered

Updated 238 days ago|11/25/2017 5:35:53 AM

1 Answer/Comment

7(x - 3) + 3(4 - x) = -8

7x - 21 + 12 - 3x = -8

4x - 9 = -8

4x = -8 + 9

4x = 1

x = 1/4

7x - 21 + 12 - 3x = -8

4x - 9 = -8

4x = -8 + 9

4x = 1

x = 1/4

Added 238 days ago|11/25/2017 5:35:53 AM

This answer has been confirmed as correct and helpful.

Score:
Solve for x.
13(x - 3) = 39
x = 1
x = 4
x = 6
x = 10 **Weegy:** Simplifying
x = -2. (More)

Question

Expert Answered

Updated 11/27/2014 9:41:24 AM

1 Answer/Comment

13(x - 3) = 39

13x - 39 = 39

13x = 39 + 39

13x = 78

x = 78/13

x = 6

13x - 39 = 39

13x = 39 + 39

13x = 78

x = 78/13

x = 6

Added 11/27/2014 9:41:22 AM

This answer has been confirmed as correct and helpful.

27,103,193

questions answered

There are no comments.